Governança hídrica e relações públicas: a qualidade da comunicação pública no Comitê de Bacia Hidrográfica do Alto do Tietê - Prates, Laís Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
A growing concern of public officials can be seen globally about how to deal effectively with the challenges arising from the sustainable exploitation of natural resources combined with productive mechanisms to the engagement of society in the formulation, implementation, execution and evaluation of public policies of that field. In Brazil, the legislation provides for the establishment of water man-agement committees, participatory arenas for water management. This research sought to understand the mediated communication processes established by the Water Management Committee of the High Tiete (CBH-AT), in the São Paulo State, and to determine strategies of communication and public relations capable of improving the dynamics of information and communication practices present in their activities. Specific objectives are: a) to investigate the digital communication mechanisms oper-ated by the CBH-AT, in order to characterize the quality of the information flows disseminated to promote the articulation of social actors and the construction of perspectives around the performance of that participatory institution; b) to characterize the different forms of mediated communication un-derpinning the interactions among the various social actors involved in CBH-AT, in order to understand the mechanisms that enable the activities of that public body and identify the procedures that help or hinder its performance as a participatory instance; c) to identify opportunities in the mediated commu-nication practices of the CBH-AT, where public relations practices may contribute to boost the perfor-mance of this space of policy deliberation.According to the results obtained, the sample of web pages, including guidelines, official announcements and CBH-AT notes, presents 17% of the information considered necessary, within the theoretical-methodological context of the research, for the compre-hensive... (Complete abstract electronic access below)

Em âmbito global, verifica-se a existência de uma crescente preocupação dos gestores públicos em lidar de forma efetiva com desafios resultantes da exploração sustentável de recursos naturais aliada a mecanismos produtivos de engajamento da sociedade na formulação, implementação, execução e avaliação de políticas públicas da área. No Brasil, a legislação determina o estabelecimento dos comitês de bacias hidrográficas, arenas participativas de gestão das águas. Esta pesquisa buscou compreender os processos de comunicação mediada estabelecidos pelo Comitê de Bacia Hidrográfica do Alto Tietê (CBH-AT), do Estado de São Paulo, e discernir estratégias de comunicação e relações públicas que possam contribuir para a consecução de seus objetivos como instância de participação democrática. Os objetivos específicos são: a) Investigar os mecanismos de comunicação digital explorados pelo Comitê de Bacia Hidrográfica do Alto Tietê (CBH-AT), com o objetivo de caracterizar a qualidade dos fluxos de informação disseminados para promover a articulação dos atores sociais e a construção de posicionamentos em torno da atuação dessa instância participativa; b) Caracterizar as diferentes formas de comunicação mediada, subjacentes às interações entre os diversos atores sociais que atuam no Comitê de Bacia Hidrográfica do Alto Tietê (CBH-AT), com a finalidade de conhecer mecanismos que viabilizam as atividades do órgão e apontar os procedimentos que podem auxiliar ou prejudicar sua atuação como instância participativa; c) identificar oportunidades, nas realizações de comunicação mediada do Comitê de Bacia Hidrográfica do Alto Tietê (CBH-AT), em que práticas de relações públicas possam contribuir para dinamizar a performance do comitê como espaço de deliberação política. De acordo com os resultados obtidos, a amostra de páginas web... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Comunicação; Relações publicas; Governança; Bacias hidrográficas - Brasil; Watersheds - Brazil